2011
DOI: 10.1146/annurev-immunol-031210-101400
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper CD4 T Cells (TFH)

Abstract: T cell help to B cells is a fundamental aspect of adaptive immunity and the generation of immunological memory. Follicular helper CD4 T (T(FH)) cells are the specialized providers of B cell help. T(FH) cells depend on expression of the master regulator transcription factor Bcl6. Distinguishing features of T(FH) cells are the expression of CXCR5, PD-1, SAP (SH2D1A), IL-21, and ICOS, among other molecules, and the absence of Blimp-1 (prdm1). T(FH) cells are important for the formation of germinal centers. Once g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
2,918
6
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,425 publications
(3,009 citation statements)
references
References 286 publications
72
2,918
6
13
Order By: Relevance
“…Tfh cells are a subset of activated CD4 1 T cells and are specialized to regulate B-cell-mediated humoral immunity [11,27]. Furthermore, a recent study suggested that persistent infection of virus could drive the differentiation of helper T cells to Tfh cells [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tfh cells are a subset of activated CD4 1 T cells and are specialized to regulate B-cell-mediated humoral immunity [11,27]. Furthermore, a recent study suggested that persistent infection of virus could drive the differentiation of helper T cells to Tfh cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Tfh cells express ICOS, CD40L, PD-1, and CXCR5 on the cell surface, but their function has not been fully elucidated. ICOS-ICOSL interaction, IL-21 and IL-6, but not IL-4, IFN-g, and TGF-b, are important for the generation of Tfh cells, suggesting that Tfh cells are a distinct subset of CD4 1 helper T cells, independent of Th1, Th2, and Th17 cells [9][10][11]. Further, PD-1 expressed on Tfh was recently found to be important for the survival and selection of B cells in the GC [12].…”
Section: Introductionmentioning
confidence: 99%
“…12 These markers contribute to the migration of T FH cells and the interaction of T FH cells with B cells to promote Bcell responses against pathogens. The binding of CXCR5 on T FH cells with its cognate ligand, CXCL-13, in GC facilitates the migration of T FH cells to B-cell follicles for their interaction with B cells.…”
Section: Characteristics Of T Fh Cellsmentioning
confidence: 99%
“…Generation of antibody after vaccination depends on follicular helper T cells (Tfh), a subset of CD4 + T cells that are specialized for providing help to B cells to support class switch recombination, affinity maturation, and B cell differentiation into long-lived plasma cells and memory cells in germinal centers (GC) in secondary lymphoid tissue. 38,39 A signature Tfh marker, CXCR5, is upregulated on naïve CD4 + T cells after antigen stimulation, permitting localization to the B cell zones of lymphoid tissue. 40,41 Mature Tfh cells expressing PD-1, ICOS and Bcl-6 provide signals for B cell survival and differentiation via CXCL13, IL-4 and IL-21 production as well as CD40L expression.…”
Section: Cd4+ T Cell Help Is Required For Antibody Developmentmentioning
confidence: 99%